Convert the equation from vertex form to standard form y=−4(x+5)2−3 .(1 point) Responses

y=16x2+160x+397
y=16x2+160x+412
y=−4x2−40x−103
y=−4x2−25x−3

1 answer

To convert the equation from vertex form to standard form, we need to expand and simplify.

Starting with the vertex form equation: y = -4(x+5)^2 - 3

Expanding:
y = -4(x^2 + 10x + 25) - 3
y = -4x^2 - 40x - 100 - 3
y = -4x^2 - 40x - 103

Therefore, the equation in standard form is:
y = -4x^2 - 40x - 103
Similar Questions
  1. Convert the equation from vertex form to standard form y = -4(x + 5)² - 3.y= -4x2 - 40x-103 y=16x2+160x+412 y= -4x2 -25x -3
    1. answers icon 1 answer
  2. QuestionConvert the equation from vertex form to standard form y=−4(x+5)2−3 .(1 point) Responses y=−4x2−25x−3 y equals
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions